School-Level Curricula for Sexuality Education in Nepal Considering International Technical Guidance on Sexuality Education 2018 - Aryal, Bhagwan; Adhikari, Anup; Sharma, Mohan Kumar (Perspectives on Higher Education, 2025)
There is an enormous need for sexuality-related information for adolescents and young people due to rapid psycho-social and bodily changes occurring during the most transitional periods of life, but there is no or less access to such information at home. The sexuality education curriculum is thus required to take the lead in schools formally. The purpose of this study was to critically analyze the current sexuality education curricula of grades 1 to 12 of the Government of Nepal (GoN) concerning International Technical Guidance on Sexuality Education (ITGSE) 2018. A desk review of the curricula of grades 1 to 12 was done. Before this, the present curriculum structure and contents related to sexuality education were understood through a discussion with curriculum planners and curriculum officers at the Curriculum Development Center (CDC), Nepal. A thorough evaluation of Nepal's current curriculum of Comprehensive Sexuality Education (CSE) for grades 1 to 12 identifies both its advantages and areas for improvement. It revealed significant flaws in the design and structure of the curriculum, including limitations on the inclusion of sexuality-related topics and a lack of vertical organization. Across the curriculum, several significant concepts and topics were not thoroughly addressed at different levels. It is critical to create a CSE curriculum that covers the whole range of sexuality-related issues, assures age-appropriate content, and fosters students' holistic awareness of sexuality and reproductive health to solve these shortcomings.